2017
DOI: 10.1097/dcr.0000000000000745
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-term Outcomes of Laparoscopic Total Mesenteric Excision for Neuroendocrine Tumors of the Rectum

Abstract: BACKGROUND: To our knowledge, no studies to date have assessed the short- and long-term outcomes of laparoscopic total mesenteric excision in patients with neuroendocrine tumors of the rectum. OBJECTIVE: The purpose of this study was to investigate the short- and long-term outcomes of patients who underwent laparoscopic rectal resection plus total mesenteric excision for rectal neuroendocrine tumors at our institution. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 26 publications
2
29
0
Order By: Relevance
“…This has also been reported and recognized as a pathological manifestation of mild-to-moderate nuclear atypia and localized disease, mostly with very small rates of metastasis to regional lymph nodes (LNs) or distant organs [2]. However, because of similar cancer-specific survival rates of rectal NET with regional or distant metastasis of rectal adenocarcinoma [35] according to some recent reports of long-term follow-up data, rectal NET is now considered a malignant disease [1,6]. As difficulty with chemotherapy has been reported [79], not only local resection but surgical resection with LN dissection around the rectum if LNs metastases are suspected must be used to achieve cure.…”
Section: Introductionmentioning
confidence: 99%
“…This has also been reported and recognized as a pathological manifestation of mild-to-moderate nuclear atypia and localized disease, mostly with very small rates of metastasis to regional lymph nodes (LNs) or distant organs [2]. However, because of similar cancer-specific survival rates of rectal NET with regional or distant metastasis of rectal adenocarcinoma [35] according to some recent reports of long-term follow-up data, rectal NET is now considered a malignant disease [1,6]. As difficulty with chemotherapy has been reported [79], not only local resection but surgical resection with LN dissection around the rectum if LNs metastases are suspected must be used to achieve cure.…”
Section: Introductionmentioning
confidence: 99%
“…1 Colonoscopy of the primary site shows a 14-mm submucosal tumor with central depression located at the anterior wall of the distal rectum endoscopic resection or dissection [13]. However, 7-18.6% of lymph node metastases come from tumors < 10 mm in size [7,14,15]. Given that most of these tumors harbor lymphovascular invasion, Matsuhashi et al emphasized the importance of evaluating lymphovascular invasion of the resected specimen [16].…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, lateral lymph node dissection is recommended for rectal cancer with muscularis propria invasion that is located distal to the peritoneal reflection [18]. Takatsu et al reported a single-center, retrospective study of the short-and longterm outcomes of curative surgery of 82 patients with rectal NET [7]. In their study, 5 of 6 patients who underwent lateral lymph node dissection had lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of rectal NETs are small and superficial, with indolent characteristics ( 8 ). Traditionally, tumor size and depth of invasion are considered important risk factors for metastasis.…”
Section: Introductionmentioning
confidence: 99%